Integration of atomically thin layers of transition metal dichalcogenides into high-Q, monolithic Bragg-cavities: An experimental platform for the enhancement of the optical interaction in 2D-materials - Knopf, Heiko; Lundt, Nils; Bucher, Tobias; Hoefling, Sven; Tongay, Sefaattin; Taniguchi, Takashi; Watanabe, Kenji; Staude, Isabelle; Schulz, Ulrike; Schneider, Christian; Eilenberger, Falk (Optical Materials Express, 2019)
We demonstrate a new approach to integrate single layer MoSe 2 and WSe 2 flakes into monolithic all-dielectric planar high-quality micro-cavities. These distributed-Braggreflector (DBR) cavities may, e.g., be tuned to match the exciton resonance of the 2Dmaterials. They are highly robust and compatible with cryogenic and room-temperature operation. The integration is achieved by a customized ion-assisted physical vapor deposition technique, which does not degrade the optical properties of the 2D-materials. The monolithic 2D-resonator is shown to have a high Q-factor in excess of 4500. We use photoluminescence (PL) experiments to demonstrate that the coating procedure with a SiO 2 coating on a prepared surface does not significantly alter the electrooptical properties of the 2D-materials. Moreover, we observe a resonance induced modification of the PL-spectrum for the DBR embedded flake. Our system thus represents a versatile platform to resonantly enhance and tailor light-matter-interaction in 2D-materials. The gentle processing conditions would also allow the integration of other sensitive materials into these highly resonant structures.
CRIS-Team Scopus Importer:2023-04-20